A scalable approach of using biomass derived glycerol to synthesize cathode materials for lithium-ion batteries. (20th October 2020) - Zhang, Jianan; Singh, Gurjap; Xu, Siqi; Hamad, Khaleel; Ratner, Albert; Xing, Yangchuan
Abstract: Glycerol, a main byproduct of biodiesel, was used as the fuel agent in a scalable flame-assisted spray pyrolysis approach to synthesize micron-size cathode materials. Single droplet combustion, particle morphology, and electrochemical performance were examined considering the effects of salt concentration, water addition, and post-annealing time on synthesizing Li(Ni1/3 Co1/3 Mn1/3 )O2 (NCM111) cathode materials. Single droplet tests showed that a sufficient amount of water in the glycerol-based precursor could delay droplet inflation and ignition. Moreover, using a two-fluid atomization nozzle, spray tests demonstrated that adding water would result in less wrinkled and more uniform particles. Nevertheless, increasing water proportion in the precursor could reduce the reaction heat, resulting in that samples prepared with water addition needed longer post-annealing time to improve their electrochemical performance. Using the precursor without water, the best performed NCM111 cathode material was synthesized with only 2 h of post-annealing. It has a discharge capacity of 163.3 mAh/g at 0.1C and 85.5% capacity retention at 1C after 100 cycles. The current work confirmed the capability of using glycerol as a sustainable fuel agent to synthesize NCM111 cathode materials, and also provided basic conditions for the development of large-scale production in the future. Highlights: A scalable flame assisted spray pyrolysis was developed using glycerol as fuel. Water addition to the precursor could hinder the droplet combustion. The electrochemical performance of NCM111 was worsened when more water was added. Using glycerol could effectively shorten the post-annealing time to 2 h. NCM111 from glycerol precursor has a discharge capacity of 163.3 mAh/g at 0.1C.